If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -1(3x + 8) = 0 Reorder the terms: 15 + -1(8 + 3x) = 0 15 + (8 * -1 + 3x * -1) = 0 15 + (-8 + -3x) = 0 Combine like terms: 15 + -8 = 7 7 + -3x = 0 Solving 7 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = 0 + -7 -3x = 0 + -7 Combine like terms: 0 + -7 = -7 -3x = -7 Divide each side by '-3'. x = 2.333333333 Simplifying x = 2.333333333
| 12x-2(6x+7)=-14 | | (x+4)(x-3)=5x | | -24x-3(-8x+2)=1 | | -x-4(2)=-5 | | 8(2x-1)-5(2x+3)=-5 | | -8-28=13-9x | | -2x+2(-3x-13)=10 | | (2x-5)2=121 | | 2x+9y=10 | | 8x+32=3x+3 | | 7(1-x)-6(2-x)=8 | | x^3-14x^2+39x+54=0 | | 3a-12a-15=0 | | 5(x+1)+5(x-1)=30 | | x+0.10x+0.05x=40 | | 10m+32m=-5 | | m-3m=-10 | | 3(x-11)(x+10)=0 | | 7(x+10)-3=73 | | x^2+15x+30=6 | | m-1/3=5/12 | | 5x+5-9x=-11 | | 2x+7+4(2X+3)=-1 | | Logy=25 | | 3/2x-14=16 | | 8-2x=1+x | | x=1.42x-60 | | 7+6p=3+2(1-p) | | x=1.42x-8 | | 17x+13y=1 | | 4x+7=7x+13 | | 4-(x+y^2)=0 |